Effect of Burning and Tillage Options on Yields in a Continuous Wheat-Double-Crop Soybean Rotation - D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 2020)
Double-crop soybean yields during the first two years of this study have not been affected by management of previous wheat straw practices by burning or tillage done before planting. However, by the second year of the study, subsequent wheat yields were 41% greater where the wheat residue had been burned the previous year.
Keywords: burning; tillage; wheat straw residue; double-crop soybean